(untitled) (The Research of Medical Science Review, 2025)
Displaced distal radial fractures (DDRFs) comprise an ordinary upper extremity injury and closed reduction along with casting is the initial management choice, especially in resource restricted condition. The proposed study will also measure the success rate of such an intervention as well as determine the demographic and clinical factors that can affect outcomes among adult patients. This is a descriptive cohort study that was done at the Department of Orthopedics Jinnah Postgraduate Medical Center, Karachi, Pakistan that was carried out between April 2019 and October 2019. Ninety adults (18 60 years) with DDRFs less than 1-week old were subjected to closed reduction under manual traction by the consultant orthopedic surgeons. Success was definitely described as union of the fracture on plain radiographs at 6 weeks and 3 months. Data on variables such as the age, gender, body mass index (BMI), fracture side were analysed using the SPSS software V20 and Chi-square tests were performed to establish association (p<0.05). Mean age of the cohort was 42.58+ 10.98 years with 66.67, % (60/90) of the sample being female. The percentage of success recorded was 93.33 (84/90). Age (p=0.647), gender (p=0.370), BMI (p=0.609), nor fracture side (p=0.091) were shown to be of any statistical significance to the outcomes. Conclusively, it is evident that closed reduction as well as manual traction has great effectiveness in treatment of DDRFs with a success rate of 93.33 %. Clinical and demographic factors had no significant effect on outcomes, which makes it an effective non-invasive methodology.